PENGARUH METODE PEMBELAJARAN GAME BASED LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DAN BUDI PEKERTI KELAS XI DI SMA NEGERI 2 TARUTUNG TAHUN PEMBELAJARAN 2025/2026 - Daniel F.N. Hutabarat; Sandy Ariawan; Maria Widiastuti; Lasmaria Lumban Tobing; Rawatri Sitanggang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the positive and significant effect of the Game-Based Learning method on the learning motivation of Grade XI students in the Christian Religious Education and Character Building subject at SMA Negeri 2 Tarutung during the 2025/2026 academic year. The research hypothesis posited that the Game-Based Learning method has a positive and significant effect on students' learning motivation. A quantitative research method employing a quasi-experimental design was used. The study population consisted of all 272 Christian students in Grade XI at SMA Negeri 2 Tarutung for the 2025/2026 academic year. The sample was selected using purposive sampling: Class XI KM 7 served as the experimental class, and Class XI KM 8 served as the control class, with 33 students in each. A 29-item learning motivation questionnaire was used as the research instrument. Data were analyzed using the N-Gain Score to measure the magnitude of the increase in learning motivation and the Paired Sample t-Test to examine differences in learning motivation before and after the intervention in the experimental class. The N-Gain Score results showed an average value of 0.5170 for the experimental class (moderate category) and 0.0987 for the control class (low category). The Paired Sample t-Test yielded a t-count of 12.687 (df = 32, Sig. < 0.001). At a significance level of α = 0.05, the t-table value was 1.697; thus, t-count > t-table (12.687 > 1.697). Consequently, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. It is concluded that the Game-Based Learning method has a positive and significant effect on the learning motivation of Grade XI students in the Christian Religious Education and Character Building subject at SMA Negeri 2 Tarutung during the 2025/2026 academic year. Keywords: Game-Based Learning Method, Learning Motivation, High School Students